Internationale Untersuchungen über Kabeljau- und Rotbarschbrut im nordwestlichen Atlantik - Kotthaus, A. (1963)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010